Nanoscale Drug Delivery Systems: From Medicine to Agriculture - Vega-Vásquez, Pablo; Mosier, Nathan S.; Irudayaraj, Joseph (Frontiers in Bioengineering and Biotechnology, 2020)
In this review, we attempt to evaluate the advantages and disadvantages of different types of colloidal nano-drug delivery vehicles developed for biomedical purposes and examine their impact on agriculture, especially for plant breeding, growth promotion, disease control and post-harvest quality control. Although several novel drug delivery concepts exist, lacking is a standard operating procedure. Further, we highlight the importance of a rational design of nano-carriers and identify current research gaps to enable application-specific scaleup for the treatment of plant diseases, controlled release of fertilizers, and plant breeding.Drug nano-delivery systems: From medicine to agriculture. The main challenges in drug delivery systems are to protect, transport and release biologically active compounds at the right time in a safe and reproducible manner, usually at a specific target site. In the past, drug nano-carriers have contributed to the development of precision medicine and to a lesser extent have focused on its inroads in agriculture. The concept of engineered nano-carriers intended for the delivery of cargo for therapeutics may be a promising route to address confounding challenges in agriculture that could perhaps lead to an increase in crop production while reducing the environmental impact associated with crop protection and food production. The main goal in this review is to evaluate the potential and point to the gaps in the development of various types of colloidal nano-drug delivery vehicles intended for biomedical purposes. A key motivation is to evaluate the potential use of these systems in agriculture, especially in the area of plant breeding, growth promotion, disease control, and post-harvest quality control. Further, we highlight the importance of a rational design of nano-carriers and identify current research gaps to enable scale-up relevant to applications in the treatment of plant diseases, controlled release of fertilizers, and plant breeding.